2022
DOI: 10.1093/jambio/lxac091
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antiaflatoxigenic mechanism activity of freeze-dried culture filtrate ofStreptomyces philanthiRL-1-178 on the two aflatoxigenic fungi and identification of its active component

Abstract: Aims The study reports the antifungal and antiaflatoxigenic mechanism activity of freeze-dried culture filtrate of Streptomyces philanthi RL-1-178 (DCF RL-1-178) against two aflatoxigenic strains (Aspergillus parasiticus and A. flavus) and identification of its active component. Methods and Results Significant inhibition in ergosterol biosynthesis by the DCF RL-1-178 appeared on the plasma membrane. Moreover, the DCF RL-1-178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Thus, this pathogen-beneficial ROS suppression effect may be driven by the pathogens themselves to scavenge ROS. It was supported by Boukaew et al, who reported that Aspergillus parasiticus and A. flavus increased tolerance to biotic stress through enhanced activities of antioxidant enzymes activities, such as POD, SOD, and CAT (Boukaew et al, 2023). However, it remains unclear how WJ561 CFS balances its ROS-mediated responses to inhibit V. pyri during infection.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, this pathogen-beneficial ROS suppression effect may be driven by the pathogens themselves to scavenge ROS. It was supported by Boukaew et al, who reported that Aspergillus parasiticus and A. flavus increased tolerance to biotic stress through enhanced activities of antioxidant enzymes activities, such as POD, SOD, and CAT (Boukaew et al, 2023). However, it remains unclear how WJ561 CFS balances its ROS-mediated responses to inhibit V. pyri during infection.…”
Section: Discussionmentioning
confidence: 95%